Prontidão de recém-nascidos prematuros para o início da alimentação oral - Ana Henriques Lima (2013)
Objectives: To identify the predictors of readiness for oral feeding in premature infants; to describe the skill levels of oral feeding in preterm newborns at the first oral diet; to identify and systematize the main studies about the transition process on feeding by gavage to full oral feeding in premature infants. Methods: The study was conducted in three stages. In the first, cross-sectional observational study was conducted with 103 premature newborns, assessed on the first oral feeding. The protocol proposed by Neiva (2008) was used for classification of newborns in able and unable to begin oral feeding. These two groups were compared according to the following variables: gestational age at birth, birthweight, Apgar 5th minute, number of days on mechanical ventilation, postconceptional age, weight and behavioral state at the first oral feeding. A logistic regression analysis was performed to know which characteristics are predictive of readiness for oral feeding. In the second study, 46 preterm infants, classified as able to begin the oral feeding were evaluated and classified into four levels of oral feeding skills, according to the performance obtained in the evaluation of the first oral feeding. To analyze the results, comparisons were made between skill levels and variables: gestational age at birth, birth weight, days of life in the first oral feeding, postconceptional age at full oral feeding, time of transition to full oral feeding, consumption and postconceptional age at discharge. Finally, was carried out a systematic review of the literature to search articles that describe the transition from gavage to oral feeding in premature infants, in the databases MEDLINE, LILACS and SciELO. Analyzes of the methodology of the studies and its main findings, as well as a meta-analysis of the effects of sensory-motor-oral stimulation on the duration of the transition to oral feeding and on the length of hospital stay were performed. Results: In the first study, the results of univariate analysis showed that the variables associated with readiness were gestational age at birth, birth weight, postconceptional age and weight at the first oral feeding. In the final model of multivariate analysis, the variables that remained associated with readiness to begin the oral feeding were postconceptional age (p=0,018) and weight at the first oral feeding (p=0,033), indicating that the increase of postconceptional age and weight increases the chance of the preterm infant be able to begin oral feeding. In the second study, it was observed that the lowest skill levels of oral feeding was associated with lower gestational age at birth, lower birth weight, longer time to oral feeding, lower consumption, longer transition to obtaining oral feeding and older corrected gestacional age at discharge. In a systematic review of the literature, 29 publications were considered. Most studies were clinical trials (44,8%) and did not use standardized scales at the beginning of the transition process (82,7%). In the meta-analysis, the effect of sensory-motor-oral stimulation is positively correlated to the length of transition to full oral feeding (p=0,000), but no statistically significant association was found with length of hospital stay (p=0,09). However, we found considerable heterogeneity between studies, both in the analysis of the length of transition to full oral feeding (I2=93,98) and length of hospital stay (I2=82,30), limiting the generalizations of the found estimates. Conclusions: The corrected gestacional age and weight at the first oral feeding are predictors of readiness for oral feeding in preterm infants. The level of skills in the first oral feeding provides important information about the whole process of transition to full oral feeding. It was not possible to determine the effect of stimulation of the sensorimotor oral system in the process of transition to full oral feeding and new studies comparing similar intervention methods should be performed.